(untitled) (Revista de Ensino em Artes, Moda e Design, 2020)
The clothing industry presenting chemical and social impacts throughout its cycle. Thus, environmental awareness about these impacts as well as their confrontation is urgent among professionals in the area. In view of this scenario, this paper aims to present the conception and action of the Fashion Design for Sustainability Teaching Project throughout 2019 at IFRS campus Erechim. For that, it uses the experience report as a method, exposing the context of creation, the procedures used and the actions implemented throughout the project. As a result, the project provided an approximation between the disciplines of courses in the Fashion area and the theme design for sustainability, fostering the environmental awareness of future professionals.